Oxygen adsorption on surfaces studied by a spin- and alignment-controlled O2 beam. Issue 1 (February 2016) - Kurahashi, Mitsunori
Abstract: Molecular oxygen (O2 ) is a paramagnetic linear molecule, yet the effect of its molecular alignment and electron spin on the dynamics of O2 adsorption has remained unclear. Recently, it has been however shown that the use of magnetic hexapolar field allows us to prepare a single spin-rotational state [( J, M ) = (2, 2)] selected O2 beam for which both the molecular alignment and the spin state of O2 are well defined. State-resolved studies of O2 sticking on Si(1 0 0), Al(1 1 1), Ni(1 1 1) surfaces conducted with this beam have clarified that the O2 sticking probability depends strongly on the molecular alignment and the spin orientation of O2 relative to the surface. The mechanism of O2 adsorption on Al(1 1 1) has been disputed in the past few decades, but the observed steric effect has provided a reasonable picture for it. The preparation method of the state-selected O2 beam and its application to the alignment- and spin-resolved O2 sticking studies are reviewed.